2015
DOI: 10.1155/2015/145305
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐146b Mediates Endotoxin Tolerance in Human Phagocytes

Abstract: A proper regulation of the innate immune response is fundamental to keep the immune system in check and avoid a chronic status of inflammation. As they act as negative modulators of TLR signaling pathways, miRNAs have been recently involved in the control of the inflammatory response. However, their role in the context of endotoxin tolerance is just beginning to be explored. We here show that miR-146b is upregulated in human monocytes tolerized by LPS, IL-10, or TGFβ priming and demonstrate that its transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Consistent with growing evidence of the relevance of regulatory mechanisms acting at the posttranscriptional level in the immune system, endotoxin tolerance has been reported to also involve specific microRNA induced by TLR agonists . A key role in this is presently recognized for miR‐146a and miR‐146b, whose ability to operate a negative feedback regulatory loop after LPS triggering by direct targeting key elements of the TLR4 signaling pathway supports their direct role in LPS self‐tolerance . MiR‐146a levels are further overexpressed when LPS challenge is followed by other TLR agonists, indicating its role also in cross‐tolerance .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Consistent with growing evidence of the relevance of regulatory mechanisms acting at the posttranscriptional level in the immune system, endotoxin tolerance has been reported to also involve specific microRNA induced by TLR agonists . A key role in this is presently recognized for miR‐146a and miR‐146b, whose ability to operate a negative feedback regulatory loop after LPS triggering by direct targeting key elements of the TLR4 signaling pathway supports their direct role in LPS self‐tolerance . MiR‐146a levels are further overexpressed when LPS challenge is followed by other TLR agonists, indicating its role also in cross‐tolerance .…”
Section: Introductionmentioning
confidence: 67%
“…This initial burst of pro-inflammatory molecules is followed at later time-points in the course of the innate immune response by the local release of anti-inflammatory cytokines, including IL-10 and TGF-β, and an increase in circulating levels of glucocorticoids, which render the host temporarily specific microRNA induced by TLR agonists [6][7][8]. A key role in this is presently recognized for miR-146a and miR-146b, whose ability to operate a negative feedback regulatory loop after LPS triggering by direct targeting key elements of the TLR4 signaling pathway supports their direct role in LPS self-tolerance [9][10][11]. MiR-146a levels are further overexpressed when LPS challenge is followed by other TLR agonists, indicating its role also in cross-tolerance [10].…”
Section: Introductionmentioning
confidence: 94%
“…STAT3 is a well-known transcriptional activator for many genes 20 , and it has been reported to inhibit gene expression as well, by promoting methylation of the target genes promoter [21][22][23] . In normal tissues STAT3 is reported to activate miR-146b transcription 24,25 . However, in several systems miR-146b promoter methylation has been shown to prevent miR-146b expression, even in the presence of constitutively activated STAT3 26,27 .…”
Section: Mir-146b Is Differentially Expressed In Cd8 Vs Cd4 T-lgls Anmentioning
confidence: 99%
“…MiRNAs bind to the 3′‐untranslated region (3′‐UTR) of mRNAs to directly regulate inflammatory factors or act on the relevant targets of the TLRs pathway, thus, mediating endotoxin tolerance . MiR‐146 is critical for endotoxin‐induced tolerance and may possibly be the most important MiRNA in endotoxin tolerance . The study showed that miR‐146a was significantly upregulated toward subsequent endotoxin stimulation and endotoxin tolerance was dependent on the endotoxin dose and the level of miR‐146a upregulation .…”
Section: The Molecular Mechanisms Of Endotoxin Tolerancementioning
confidence: 99%